Efektifitas Metode Forward Chaining Untuk Meningkatkan Keterampilan Memasang Baju Berkancing Bagi Anak Cerebral Palsy - Riani, Rani; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2021)
This study aims to prove the effetiveness of the forward chaining method to improve the skills of putting on button-up shirts for children with cerebral palsy. The research method that the resercher uses is asingle subject research (SSR) with an A-B-A designe. The data analysis technique is described in the from of visual and grafhic analysis. the subjact by the researcher were children with cerebral palsy with initials BI class II at SLB Negeri 1 Kepahiang. The process of observing the research was carried out on the skills of installing clothes with large buttons, medium buttons and finally, small buttons in three sessions, namely the baseline conditions A1, B, and A2. A1 was performed 4 times, while the interventions condition (B) was carried out 12 times on large buttons, 6 times on medium buttons, and 8 times on small buttons. Followed by yhe last session (A2) conducted 4 times on different days. So it was found that the forward chaining method was proven to be effective in improving the skills of putting on button-up clothes for children with cerebral palsy.